Heat transfer during multiple droplet impingement and spray cooling: Review and prospects for enhanced surfaces. (October 2021) - Benther, J.D.; Pelaez-Restrepo, J.D.; Stanley, C.; Rosengarten, G.
Highlights: The connection between multiple droplet impingement and spray cooling are reviewed. Fundamentals, the state-of-the-art and surface enhancement for both multiple droplet impingement and spray cooling are discussed. Recent advances in numerical analyses allow additional data for analysing the effect of enhanced surfaces during impingement. Spray cooling systems combined with enhanced surfaces is shown to be a promising method to remove high heat fluxes. Abstract: Many systems require very high heat removal rates in small areas due to the increase in their packing density, such as power electronics. These systems need to be cooled to maintain functional operating temperatures. Additionally, metal quenching requires rapid cooling to obtain specific desirable properties of the cooled metal. Spray cooling is one of the most effective heat transfer techniques capable of dealing with high heat flux and temperatures. Multiple droplet impingement offers a simplified process of the fundamentals of spray cooling in a controllable system, and offers the ability to isolate and investigate the influence of different parameters. This article focuses on the improvements in spray cooling obtained by modifying the heated surface (commonly referred to as an enhanced surface). We present a review of multiple droplet impingement heat transfer, and the effects of the characteristics of different surfaces on spray cooling performance. Our findings show that multiple droplet impingement studies present useful but not complete insights that can help to advance spray cooling understanding. Moreover, enhanced surfaces can boost the outcome of spray cooling in different ways that depend on the temperature of the surface relative to the saturation temperature of the liquid and the spray inclination. However, there remains a need for further investigation, and the present work discusses several possibilities.